A Notch‐dependent transcriptional hierarchy promotes mesenchymal transdifferentiation in the cardiac cushion. Issue 7 (17th April 2014) - Chang, Alex C.Y.; Garside, Victoria C.; Fournier, Michele; Smrz, Justin; Vrljicak, Pavle; Umlandt, Patricia; Fuller, Megan; Robertson, Gordon; Zhao, Yongjun; Tam, Angela; Jones, Steven J. M.; Marra, Marco A.; et al.
<x xml:space="preserve">Abstract</x> Background: Valvuloseptal defects are the most common congenital heart defects. Notch signaling–induced endothelial‐to‐mesenchymal transition (EMT) in the atrioventricular canal (AVC) cushions at murine embryonic day (E)9.5 is a required step during early valve development. Insights to the transcriptional network that is activated in endocardial cells (EC) during EMT and how these pathways direct valve maturation are lacking. Results: We show that at E11.5, AVC‐EC retain the ability to undergo Notch‐dependent EMT when explanted on collagen. EC‐Notch inhibition at E10.5 blocks expression of known mesenchymal genes in E11.5 AVC‐EC. To understand the genetic network and AVC development downstream of Notch signaling beyond E9.5, we constructed Tag‐Seq libraries corresponding to different cell types of the E11.5 AVC and atrium in wild‐type mice and in EC‐Notch inhibited mice. We identified 1, 400 potential Notch targets in the AVC‐EC, of which 124 are transcription factors (TF). From the 124 TFs, we constructed a transcriptional hierarchy and identify 10 upstream TFs within the network. Conclusions: We validated 4 of the upstream TFs as Notch targets that are enriched in AVC‐EC. Functionally, we show these 4 TFs regulate EMT in AVC explant assays. These novel signaling pathways downstream of Notch are potentially relevant to valve development. Developmental Dynamics 243:894–905, 2014. © 2014 Wiley Periodicals, Inc.